Impact of atrial fibrillation and biventricular pacing percentage on long-term outcome in patients with heart failure treated with cardiac resynchronization therapy. (14th October 2021) - Neves Pereira, M; Leite, P.V.H; Dias, G; Cardoso, A.F; Tinoco, M; Azevedo, O; Ribeiro, S; Ferreira, F; Sanfins, V; Lourenco, A
Abstract: Introduction: A history of preoperative atrial fibrillation (AF) has been found to be associated with unfavorable outcomes, higher risks of non-response to cardiac resynchronization therapy (CRT) and loss of biventricular pacing (BivP). We aimed to assess the impact of AF and BivP on long-term outcomes in heart failure patients treated with CRT. Methods: We retrospectively enrolled 227 patients undergoing CRT implantation between 2013 and 2020 according to the current guidelines. 118 patients were included in our analysis, from whom all data were available. Clinical, electrocardiographic and echocardiographic parameters were evaluated at baseline and 6 months after CRT. Response to CRT was defined as an increase in left ventricular ejection fraction (LVEF) >10%. We considered an effective delivery of BivP >98%. The primary endpoint was the composite endpoint of hospitalization due to HF or death for any cause. Results: 118 patients were included (mean age 69±11 years, 66.1% males, 39.8% ischemic etiology; baseline LVEF was 27, 6±6%). Patients were divided into AF (n=42; 35, 6%) and sinus rhythm (SR (n=76); 18 patients had permanent AF. AF patients had higher index left atrial volume and left ventricular mass (p<0.001). Mean follow-up time was 43±18 months. BivP percentage was significantly superior in SR than in AF patients (98.1±2.1% vs 94.7±4.5%, p<0.001), with 75% of SR patients having BivP>98% vs 30, 3% of AF patients (p<0.001). There were no differences in preoperative parameters between them. The response rate to CRT was higher in SR patients when compared to AF patients (63, 2% vs 40, 5%, p=0.021). Indeed, the variation of LVEF was higher in SR patients (12±10% vs 7±9%, p=0.012). During follow-up, there were significant differences between AF and SR patients in the primary endpoint (73, 8% vs 42, 6%, p<0.001), and mortality for any cause (26, 2% vs 9, 2% p=0.014; p<0.001). In a multivariate logistic regression analysis pre-procedural AF and BivP (%) were the only independent predictors of primary endpoint (HR 8.949, 95% CI 2.429 – 32.972, p=0.001; HR 0.719, 95% CI 0.526 – 0.982, p=0.038, respectively). Kaplan-Meier curves showed that event survival free was higher in SR patients when compared to AF (69±4 vs 24±3 months, p<0.001) Conclusion: Pre - procedural AF and BivP are independent predictors of the occurrence of a primary endpoint of hospitalization due to HF or death for any cause in HF patients submitted to CRT. Funding Acknowledgement: Type of funding sources: None.